An analysis on conflict management between politicians and public managers in public sector Zimbabwe, The case of Masvingo City Council: 2008 to 2014 - Marutsvaka, Johanes (Midlands State University, 2017)
Conflict is inevitable at any given organisation, society, community, groupings, and associations even among family members. The inevitability of conflict is not worthy to be ignored but worthy to be given much attention to be managed. Trying to ignore and deny the existential of conflict within organisations or among individuals will be like ignoring a drop of acid on your own body. Management of conflict is a necessity especially in the public sector. The public sector in Zimbabwe is prone to a vast outbreak of conflict and the worst negativity of them can be witnessed if there be any deficiency of proper conflict management. The existential of conflict within public sector between politicians and public managers is of no question. This is due to various causes which are outlined in this research such as power struggle, political parties, government system, media and pressure groups. With proper management positive results can be confidently yield and that’s the main thrust of this research to examine and analyse the conflict management process in the public sector between politicians and public managers from 2008 to 2014. The paper aimed at knowing the strategies utilised in conflict management and at the same time proffer the possible solutions to challenges thereon.